The sustainability of the historical centres at the dawn of the XXI century - González González, María Jesús (Anales de Geografía de la Universidad Complutense, 2007)
Studies on the city come including multiple and diverse aspects, which gives rise to the fact that the urban phenomenon becomes something more everytime is something more complex. The study of historical centers of the cities, which, perhaps due to because of considering them as «a consolidated urban phenomenon», or perhaps for other diverse reasons, has not been an object of study of increasing attention with respect to sustainable development. Nevertheless, they are places of great interest; susceptible of transformations and innovations; places of great social interaction, an interaction that varies depending on times, because they are generally inhabited by certain individuals: their residents; used, consumed and enjoyed by others, in relation to its functionality, mainly of tourism, leisure and culture. It is a phenomenon whose characteristics and peculiarities are shared by many historical centers of average cities of the south of Europe. This work tries to show the specific and general problems of the urban historical centers and their own articulation.